2013
DOI: 10.1523/jneurosci.4714-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation (tDCS) of Left Parietal Cortex Facilitates Gesture Processing in Healthy Subjects

Abstract: Gesture processing deficits constitute a key symptom of apraxia, a disorder of motor cognition frequently observed after left-hemispheric stroke. The clinical relevance of apraxia stands in stark contrast to the paucity of therapeutic options available. Transcranial direct current stimulation (tDCS) is a promising tool for modulating disturbed network function after stroke. Here, we investigate the effect of parietal tDCS on gesture processing in healthy human subjects. Neuropsychological and imaging studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Interestingly, a previous study by Weiss et al . () using transcranial direct current stimulation (tDCS) found that anodal stimulation over left area PFm improved participants’ gesture matching ability. However, the authors suggested that their result could have been driven by a combined effect of SMG and AG stimulation, considering the central position of PFm and the size of tDCS electrodes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, a previous study by Weiss et al . () using transcranial direct current stimulation (tDCS) found that anodal stimulation over left area PFm improved participants’ gesture matching ability. However, the authors suggested that their result could have been driven by a combined effect of SMG and AG stimulation, considering the central position of PFm and the size of tDCS electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Weiss et al . () stated that both parts of the IPL may have to be stimulated simultaneously in order to facilitate gesture matching. Considering our results, the same could be true for influencing gesture imitation and further highlights the importance of considering in detail the role of different regions of the IPL, along with their interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding novel techniques to improve rehabilitation in fine movements in the trained hand as well as transfer of learning into the untrained hand would implicate for patients who struggle with fine motor tasks, such as those with stroke or Parkinson’s disease. Recently, anodal transcranial direct current stimulation (a-tDCS), which modulate brain activity, has allowed direct investigation of the role of specific areas of the brain during different stages of sequence learning (Nitsche et al, 2003; Fregni et al, 2005; Reis et al, 2009; Schambra et al, 2011; Zaehle et al, 2011; Javadi and Walsh, 2012; Pope and Miall, 2012; Hoy et al, 2013; Saucedo Marquez et al, 2013; Weiss et al, 2013; Convento et al, 2014; Waters-Metenier et al, 2014; Reis et al, 2015; Rivera-Urbina et al, 2015). …”
Section: Introductionmentioning
confidence: 99%